2014
DOI: 10.1108/cms-09-2011-0066
|View full text |Cite
|
Sign up to set email alerts
|

Impact of financial capability on firms’ competitiveness and sustainability

Abstract: Purpose – The purpose of this paper is to investigate the impact of different sources of external financing and internal financial capabilities on competitiveness and sustainability. This paper also studies the nature of their relationships related to regulations on external financing in Chinese capital market. Design/methodology/approach – Resource- and industry-based views provide a theoretical background. Based on balanced panel of 4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 79 publications
1
24
0
5
Order By: Relevance
“…Having enough finance enables SMEs to boost their operational activities effectively. For instance, Fonseka et al, [31] demonstrate that out of many resources, financial capital is the most prominent for SMEs in emerging economies. Moreover, Cooper, Gimeno-Gascon and Woo [32] also describe that human and financial capital help newly established ventures as a shield to respond to the external threats and changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having enough finance enables SMEs to boost their operational activities effectively. For instance, Fonseka et al, [31] demonstrate that out of many resources, financial capital is the most prominent for SMEs in emerging economies. Moreover, Cooper, Gimeno-Gascon and Woo [32] also describe that human and financial capital help newly established ventures as a shield to respond to the external threats and changes.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some firms are unable to enter into profitable markets due to a lack of finance. Thus sufficient finance encourages them to seize the benefits of new markets [31]. Adequate financial capital facilitates firms in opportunity recognition that is helpful for efficiency e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Financial capabilities can play a dynamic role in integrating other resources and skills and allow SMEs to deal with competitive business activities (Fonseka, Tian, & Li, 2014). A firm's strategy and success fundamentally depend on timing, availability, and effective and efficient use of financial resources in the development and investment phase.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…However, these resources require financial abilities to transform the resource and development of new products (Zou, Chen, & Ghauri, 2010). Despite this, many scholars give minor attention to financial resources even it has a vital character in the attainment of CA (Fonseka et al, 2014). Furthermore, it is revealed that a successful firm maintains its sustainable growth in the long run which increases the process of victory in its financial competences too (Raisch & Von Krogh, 2007 (Muhammad & Ismail, 2009;Tandon et al, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%